ANALISIS TERHADAP PERAN ORANG TUA DALAM MEMBERIKAN PENDAMPINGAN PEMBELAJARAN DARING - Avita Khoiru Nisa (AL-MUADDIB: Jurnal Kajian Ilmu Kependidikan, 2021)
Covid 19 began to spread to the State of Indonesia in 2020 it still could not find a solution to break the chain of spread of covid 19 until now,  parenting  parents  in  accompanying and educating children to learn while at home..  The method used in this study is qualitative research with a case study approach that describes the parenting of parents in accompanying children to study at home during the covid-19 pandemic.  Based on  the results of the discussion and research above,,  there is  asituation ofthe covid 19 pandemic has changed the order of life from various aspects.  Included in online learning activities at home, college law number 12 of 2012, article 31 on distance education (PJJ) Learning that was once done in school is now studied at home.  However, online learning poses many challenges.  Parenting applied by parents has been as much as possible given to children, parents always want to make their children the best in the educational process to instill values and foster the child's spiritual intelligence, by always trying to accompany their children to learn regularly and parents also always provide supervision and restrictions to children so that children do not always play gadgets that will later result in gadget addiction